2021
DOI: 10.1021/acs.inorgchem.0c03072
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Effect of Ni2P and MXene Enhances Catalytic Activity in the Hydrogen Evolution Reaction

Abstract: Developing highly efficient non-precious electrocatalytic materials for H 2 production in an alkaline medium is attractive on the front of green energy production. Herein, we successfully designed an electrocatalyst with superb hydrophilicity, high conductivity, and a kinetically beneficial structure using Ni 2 P/MXene over a 3D Ni foam (NF) for the alkaline hydrogen evolution reaction (HER) based on the laboratory and computational research works. The designed self-supported and highly effective electrocataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 59 publications
0
40
0
Order By: Relevance
“…It is easy to find that P element is mainly concentrated in spherical-like particles in HAADF image, while N element has a larger distribution area. Herein, the distribution of N element is caused by the following reasons: 1) Nitriding treatment of Ti 3 C 2 T x would result in the substitution of functional groups (e.g., F, O, OH), [17,18] and N-doped Ti 3 C 2 T x has also been proved to have better catalytic activity and conductivity; [17,19] 2) Co 2 N as another N-containing phase is mainly distributed around spherical-like Co 2 P in the form of nanoparticles by comparing the distribution of N with those of Co and P, which can be more clearly demonstrated in Figure S2g (Supporting Information); 3) Part of N element is doped into the lattice of Co 2 P to form N-doped Co 2 P, which has been reported that N-doped Co 2 P with defects displays more active edge sites and is instrumental in HER. [20] All in all, there are multitudinous catalytic active sites on the multiheterojunction interfaces constructed by Co 2 N and Co 2 P on Ti 3 C 2 T x surface, and the well-designed 3D porous structure also exposes much more edges and defects forming an easily approachable interface for ions exchange during the electrocatalytic process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is easy to find that P element is mainly concentrated in spherical-like particles in HAADF image, while N element has a larger distribution area. Herein, the distribution of N element is caused by the following reasons: 1) Nitriding treatment of Ti 3 C 2 T x would result in the substitution of functional groups (e.g., F, O, OH), [17,18] and N-doped Ti 3 C 2 T x has also been proved to have better catalytic activity and conductivity; [17,19] 2) Co 2 N as another N-containing phase is mainly distributed around spherical-like Co 2 P in the form of nanoparticles by comparing the distribution of N with those of Co and P, which can be more clearly demonstrated in Figure S2g (Supporting Information); 3) Part of N element is doped into the lattice of Co 2 P to form N-doped Co 2 P, which has been reported that N-doped Co 2 P with defects displays more active edge sites and is instrumental in HER. [20] All in all, there are multitudinous catalytic active sites on the multiheterojunction interfaces constructed by Co 2 N and Co 2 P on Ti 3 C 2 T x surface, and the well-designed 3D porous structure also exposes much more edges and defects forming an easily approachable interface for ions exchange during the electrocatalytic process.…”
Section: Resultsmentioning
confidence: 99%
“…A widely used method was used to convert reference electrodes to a reversible hydrogen electrode (RHE) scale. [ 18 ] The scan rate was 5 mV s −1 for the linear sweep voltammetry (LSV) measurements, and 90% i R‐compensation was also considered. Electrochemical impedance spectroscopy (EIS) measurements were conducted at the frequency range from 1 000 000 to 0.01 Hz in ‐0.1 V. The cyclic voltammetry (CV) was conducted at various scan rates (10–60 mV s –1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The as-prepared samples consist of porous nanosheets, which are in single crystalline structure with a preferential [100] orientation. DFT calculation disclosed that on CoP ( Lv et al, 2021 ) facets, a near-zero Gibbs free energy could lead to high utilization efficiency of active sites, therefore endowing ( Lv et al, 2021 ) highly active CoP. In addition to single crystalline, other crystallines are, of course, affected by the crystal surface.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the heterostructure of Ni 3 N-Ni 2 P-BP catalysts can remarkably enhance the OER activity. As another promising 2D material, transition metal carbides and nitrides (known as MXenes) with the features of great mechanical stability, high conductivity, and wide chemical variety display great potential as substrates ( Du et al, 2018 ; Yoon et al, 2019 ; Lv et al, 2021 ). For example, Yan et al successfully prepared novel CoP nanosheet arrays on the surface of Ti 3 C 2 MXene nanosheets (CoP/Ti 3 C 2 MXene) ( Figure 2I ) ( Yan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] As an ideal secondary energy carrier, hydrogen only emits water during its use and does not emit other harmful gases or solid particles. 5,6 Hydrogen evolution reaction (HER) provides a promising path to generate high-purity hydrogen toward energy and environmental sustainability. 7 Currently, one of the challenging issues in HER is to explore earth-abundant, long-term available, corrosion resistant, and e cient electrocatalysts for the practical application of hydrogen-energy technology.…”
Section: Introductionmentioning
confidence: 99%